Multicompartment compliance aids in the community: the prevalence of potentially inappropriate medications. (31st January 2017) - Counter, David; Stewart, Derek; MacLeod, Joan; McLay, James S.
Abstract : Aims: To assess the prevalence of potentially inappropriate medications (PIMs) use in a population of community‐based multicompartment compliance aid (MCA) users in north‐east Scotland. Methods: Data for MCAs dispensed by 48 of the 50 community pharmacies in Aberdeen City between 1 st June to 31 st October 2014, together with concurrently prescribed medications, patient demographics and Carstairs index of social deprivation were recorded. Drug‐specific quality indicators for PIMs from the Swedish National Board of Health and Welfare were applied and bivariate logistic regression analysis used to assess for associations with demographic variables. Results: The median age was 82 years (range 12–105 years, 59% female). A total of 1977 PIMs were identified affecting 57.8% of patients. A quarter of patients were prescribed ≥10 medications and 43% had a prescription containing at least one clinically significant drug–drug interaction (DDI). Ten drug groups accounted for 76% of all DDIs. A significant increase in the risk for at least one PIM was associated with female sex (for all indicators of PIM use), age <80 years (three or more psychotropic medicines [OR 5.88, 2.96–11.70, P < 0.001]) and lower socioeconomic status (prescription of ≥10 medications [OR: 1.43, 95% CI: 1.16–1.78], prescription of a long‐acting benzodiazepine [OR: 1.84, CI: 1.14–2.98]). Conclusions: MCA use is associated with a significant incidence of PIMs particularly affecting those younger than 80 years and those living in deprived areas. Our findings indicate the need for a more aggressive multidisciplinary approach to the review of the medications prescribed to MCA users.